Tax plan to improve tax collection in the distrital municipality of Motupe - Ríos Cubas, Martín Alexander (2021)
The present investigation entitled tax plan to improve tax collection in the District Municipality of Motupe, 2019 sets as a general objective Propose a tax plan to improve tax collection in the district municipality of Motupe, 2019, for which an investigation of you descriptive, with a non-experimental design - transversal. A population of 5 workers of the Tax Collection Unit was applied to which a survey was applied, with Likert measurement scale in 5 levels. The results show that the projection of income from payment of taxes from 2017 to 2018 has been negative. With regard to Property Tax, it had a fall of - 0.16%, in public shows -0.02%, in Rate -0.09. Only in the Alcabala tax, it had an increase of 0.27%. Finally, he concludes that Tax planning would definitely contribute to improving collection rates, since only 40% consider that tax payments are planned. It is necessary to improve these indicators, where at least 80% of planning of the payment of taxes by the Municipality is achieved.